Karakteristik Agresivitas dan Etologi Anjing Kintamani Bali dalam Respon terhadap Stimulus Lingkungan - Ni Wayan Pradnya Mahayani Suardika; Wahyuni Rizki; Putu Anindya Elvaretta; Desak Made Ratih Arie Kalindi; Channah Uneputty; Ni Putu Gita Saraswati; Aathifah Fawnia Rahmaniya; Blessya Millitya Lovity Loho (PT. Saha Kreasi Indonesia, 2025)
This study examines the aggression and behavioral traits of the Kintamani Bali dog, an indigenous Indonesian breed. Observations and research suggest that their violent behavior primarily stems from a protective impulse towards territory and masters, rather than from unrestrained antagonism. Kintamani dogs exhibit vigilance, courage, and are well-suited for guarding purposes. Comprehending their behavior is crucial for effective training and conservation initiatives. Ultimately, aggressiveness emerges as a beneficial characteristic that enhances the breed's identity and purpose.